Responsible Environmental Behaviour of Secondary School Students in Relation to their Locus of Control and Achievement Motivation - Bajwa, Sukhwant; Goyal, Shalu (INDIAN EDUCATIONAL REVIEW, 2011)
The aim of the present study was to study Responsible Environmental Behaviour of Secondary School Students in relation to their Locus of Control and Achievement Motivation. The findings reveal that there exists significant relationship between Responsible Environmental Behaviour and Locus of Control. Further it was found that Internal Locus of Control group students have better responsible environmental behaviour and developed more civic action, educational action, financial action, legal action, physical action, and persuasive action as compared to External Locus of Control group students. It was also found that there exists significant relationship between Responsible Environmental Behaviour and Achievement Motivation. Further it was found that High Achievement Motivation group students have better Responsible Environmental Behaviour and developed more Civic action, Educational action, Financial action, Legal action, Physical action, Persuasive action as compared to Low Achievement Motivation group students.